Analisis Segitiga Kebijakan dan SWOT Penanganan Pandemi Covid-19 di Kabupaten Sragen - Naufal Azaki (Spirit Publik: Jurnal Administrasi Publik, 2022)
The Covid-19 pandemic that hit Indonesia and the world requires extra careful, strict and measured handling. The Sragen Regency Government as one of the autonomous regions has the obligation to control the level of spread and impact of the Covid-19 pandemic through various policy instruments, ranging from regulations, institutions, budgets to implementing apparatus in the field. This study aims to analyze various policies for handling Covid-19 in Sragen Regency uses a qualitative approach with the Strength, Weakness, Opportunity, Threat (SWOT) methods and the policy triangle analysis. The data used in the form of secondary data obtained from various official government releases to media coverage from March 2020 to December 2021. The results of the mapping of regulations and policies are constructed into a policy triangle which includes actors, context and content and then analyzed using SWOT. The results of the analysis resulted in various strategic models which were narrated into 4 matrices which substantially covered the acceleration of vaccination through community collaboration, the development of Sragen Smart Governance, wider and firm socialization activities, institutional coordination between OPD and other local governments, acceleration of ratification and enforcement of Regional Regulation concerning Discipline of Health Protocols, to the consolidation of social safety net schemes and the provision of clean water in drought-stricken areas for the implementation of health protocols. The strategy model is expected to be a feedback for decision making for the Sragen Regency Government.